The Marburg virus disease in Ghana: psychological impact of quarantine on health workers in the Adansi-North district - George Adjeisah Adjei; Grace Adjei Okai; Herman Kofi Nuake Agboh; Lawrence Ofosu Adjare; Henry Dzackah (BMC Psychology)
Abstract Background This study aimed to explore the psychological impact of quarantine on health workers during the outbreak of the Marburg disease. The study also explored the coping strategies adopted during the period of quarantine. Methods The study uses a qualitative research approach and a purposive sampling procedure to recruit healthcare workers who were quarantined due to their exposure to patients infected with Marburg virus disease for in-depth interviews. The interviews were conducted using a semi-structured interview guide. The study was conducted in one facility in the Adansi-North district. The data collected was transcribed and analyzed thematically. Results Most of the participants reported symptoms of psychological distress such as anxiety and fear as well as sleep disturbances during the period of quarantine. After the quarantine period, health workers adopted some behavioral changes such as frequent handwashing, wearing of nose masks and examination gloves. Some coping strategies adopted by the respondents during the period of quarantine include communicating with family and friends, cooking and watching television. Conclusion The findings of the study are important for policy development, especially in the area of providing access to mental health services during and after quarantine by health facilities in which healthcare professionals work. Health workers who are not quarantined should be encouraged to check on their quarantined colleagues and not stigmatize such individuals.